Characterization of the tracrARN-DRARN genetic complex associated with the CRISPR-Cas9 system of the phytosymbiont Acholeplasma palmae: biotechnological interest - Moncayo, Luis; Castro, Alex; Arcos, Diego; Centanaro, Paulo; Vaca, Diego; Maldonado, Cristina; Perez, Aleivi; Lossada, Carla; González-Paz, Lenin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The CRISPR-Cas9 technology used in plant biotechnology is based on the use of Cas9 endonucleases to generate precise cuts in the genome, and a duplex consisting of a trans-activating CRISPR RNA (tracrRNA) and a CRISPR RNA (DRRNA) which are precursors of guide RNA (sgRNA) commercially redesigned (sgRNA-Cas9) to guide gene cleavage. Most of these tools come from clinical bacteria. However, there are several CRISPR-Cas9 systems in environmental microorganisms such as phytoendosymbionts of plants of the genus Acholeplasma. But the exploitation of these systems more compatible with plants requires using bioinformatics tools for prediction and study. We identified and characterized the elements associated with the duplex in the genome of A. palmae. For this, the protein information was obtained from the Protein Data Bank and the genomics from GenBank/NCBI. The CRISPR system was studied with the CRISPRfinder software. Alignment algorithms and NUPACK software were used to identify the tracrRNA and DRRNA modules, together with various computational software for genetic, structural and biophysical characterization. A CRISPR-Cas system was found in A. palmae with type II-C characteristics, as well as a thermodynamically very stable duplex, with flexible regions, exhibiting a docking power with Cas9 thermodynamically favored. These results are desirable in programmable gene editing systems and show the possibility of exploring native molecular tools in environmental microorganisms applicable to the genetic manipulation of plants, as more research is carried out. This study represents the first report on the thermodynamic stability and molecular docking of elements associated with the tracrRNA-DRRNA duplex in the phytosymbiont A. palmae.